Effect of seed soaking and foliar application with Bilirubin on growth and yield wheat - Nasserallah, Adel Yousif; Al- Hilfy, Intsar Hadi; Zeboon, Najat Hussein (Journal of Kerbala for Agricultural Sciences, 2018)
A field experiment was conducted during 2012 – 2013 winter seasons at the Experimental Farm , Dep. of Field Crop, College of Agriculture University of Baghdad to study effect of Bilirubin on some growth , yield and quality of wheat traits var Abu – Ghraib – 3, in RCBD with three replicate , the experiment involved seven treatment :control, seed soaking with 0.25,0.50 and 1ml L-1 concentration , shoot spraying foliar with 0.25, 0.50 , and 1ml L-1 concentration in tillering and flowering stages .The results show that soaking treatment with 1ml L-1 concentration was superior on most of growth , yield ( plant high ,flag leaf area ,number of tillers ,biological yield ,number of grains,grain1000 weight ,grain yield and increasing ( 1.08, 2.45 , 47.5, 35.13, 22.78 , 0.57, 28.32 ) % contrast with control treatment respectively , while foliar treatment with 0.25ml L-1 on number of spike ,protein and gluten ratio was 730.0 spike m-2 ,12.44% and 32.15% contrast with control treatment which gave 495.0 spike m-2 , 9.87% and 28.13 %.